2014
DOI: 10.1002/0471140864.ps2807s76
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Methods for Producing Disulfide Bonds in Peptides and Proteins to Study Folding Regulation

Abstract: Disulfide bonds play a critical role in the folding of secretory and membrane proteins. Oxidative folding reactions of disulfide bond-containing proteins typically require several hours or days, and numerous misbridged disulfide isomers are often observed as intermediates. The rate-determining step in refolding is thought to be the disulfide-exchange reaction from nonnative to native disulfide bonds in folding intermediates, which often precipitate during the refolding process because of their hydrophobic prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The digested peptide fragments were analyzed by HPLC (GL Science) equipped with a COSMOSIL 5C 18 -AR-II column (Nacalai Tesque) pre-equilibrated with 5% acetonitrile in 0.05% TFA and eluted with a linear acetonitrile gradient ranging from 5% to 65% at a rate of 1%/min, with detection at an absorbance of 220 nm. The molecular masses of separated peptides were determined by MALDI-TOF MS (Bruker Daltonics) (36,37). Synthetic peptides were prepared by the Fmoc (N-(9-fluorenyl)methoxycarbonyl) solid phase method, modified with AMS, and analyzed by HPLC and MALDI-TOF MS as described previously (5,34,37).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digested peptide fragments were analyzed by HPLC (GL Science) equipped with a COSMOSIL 5C 18 -AR-II column (Nacalai Tesque) pre-equilibrated with 5% acetonitrile in 0.05% TFA and eluted with a linear acetonitrile gradient ranging from 5% to 65% at a rate of 1%/min, with detection at an absorbance of 220 nm. The molecular masses of separated peptides were determined by MALDI-TOF MS (Bruker Daltonics) (36,37). Synthetic peptides were prepared by the Fmoc (N-(9-fluorenyl)methoxycarbonyl) solid phase method, modified with AMS, and analyzed by HPLC and MALDI-TOF MS as described previously (5,34,37).…”
Section: Methodsmentioning
confidence: 99%
“…The molecular masses of separated peptides were determined by MALDI-TOF MS (Bruker Daltonics) (36,37). Synthetic peptides were prepared by the Fmoc (N-(9-fluorenyl)methoxycarbonyl) solid phase method, modified with AMS, and analyzed by HPLC and MALDI-TOF MS as described previously (5,34,37).…”
Section: Methodsmentioning
confidence: 99%
“…Since post-translational modifications mainly occur at the termini of peptides, EPL is a plausible approach to obtain functional peptides [91,92]. When a disulphide bond pattern is essential, (re-)folding of the protein is advised and oxidative folding is performed [93,94,95,96]. In a first attempt, oxidative folding is often employed in a direct manner, i.e.…”
Section: Production Of Plant Defensinsmentioning
confidence: 99%
“…In this work, we found that the condition of low pH (6.8) and low temperature (4 °C) were the optimum conditions for refolding of µ-TRTX-Hl1a. A variety of chemical additives, e.g., urea, guanidine hydrochloride (Gu/HCl), and arginine, could improve refolding of disulfide-coupled proteins [ 22 ]. The refolding was increased from 8.52% to 10.38% with the addition of 0.5 M L -Arg, but greatly increased the complexity of refolded protein.…”
Section: Discussionmentioning
confidence: 99%